2011
DOI: 10.5897/ajpp10.266
|View full text |Cite
|
Sign up to set email alerts
|

Wound healing potential of the ethanolic extracts of Bidens pilosa and Ocimum suave

Abstract: The ethanolic extracts of Bidens pilosa and Ocimum suave were evaluated for their wound healing potential on excision wound models in Wistar albino rats. A total of nine (n=9) rats per group were used to assess the wound healing potential of the extracts. There were four groups of animals treated topically twice a day with either of the following: O. suave, B. pilosa, neomycin sulfate or distilled water. The rate of wound contraction, epithelialization, and complete healing were assessed over the experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 11 publications
1
14
0
7
Order By: Relevance
“…Hassan and colleagues investigated the wound healing potential of B. pilosa in Wistar rats [127]. Mirroring the positive control neomycin sulfate, the ethanol extract of B. pilosa had faster wound closure than control rats 3, 6, and 9 days after topical application.…”
Section: Pharmacological Propertiesmentioning
confidence: 99%
“…Hassan and colleagues investigated the wound healing potential of B. pilosa in Wistar rats [127]. Mirroring the positive control neomycin sulfate, the ethanol extract of B. pilosa had faster wound closure than control rats 3, 6, and 9 days after topical application.…”
Section: Pharmacological Propertiesmentioning
confidence: 99%
“…Though there are reports on the analgesic (Makonnen et al, 2003a), antipyretic, (Makonnen et al, 2003b), gastric cytoprotective antiulcer effects on acute gastric ulcer (Tan et al, 2002) and healing effects on chronic acetic acid-induced gastric ulcers (Tan et al, 2005), mosquito repellent (Seyoum et al, 2002), antimicrobial (Runyoro et al, 2010) and wound healing activity (Hassan et al, 2011), its anti-inflammatory activity has not yet been confirmed scientifically. The present study was, therefore, carried out to evaluate the anti-inflammatory activities of the crude leaf extracts and some fractions of Ocimum suave.…”
Section: Introductionmentioning
confidence: 99%
“…The leaves extract of O. suave has been reported to exhibit the mosquito repellent ( 11 ), acaricidal ( 12 ), anti-inflammatory ( 13 ), antidiabetic ( 14 ), wound healing and anti-ulcer activities ( 8 , 15 , 16 ). It has also been shown to possess analgesic and antipyretic activities.…”
Section: Introductionmentioning
confidence: 99%